2004
DOI: 10.1007/s00259-004-1495-z
|View full text |Cite
|
Sign up to set email alerts
|

Scatter modelling and compensation in emission tomography

Abstract: In nuclear medicine, clinical assessment and diagnosis are generally based on qualitative assessment of the distribution pattern of radiotracers used. In addition, emission tomography (SPECT and PET) imaging methods offer the possibility of quantitative assessment of tracer concentration in vivo to quantify relevant parameters in clinical and research settings, provided accurate correction for the physical degrading factors (e.g. attenuation, scatter, partial volume effects) hampering their quantitative accura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
135
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(142 citation statements)
references
References 45 publications
0
135
0
2
Order By: Relevance
“…2 showed that the TEW could make it possible. Our method corresponds to Zaidi et al (8) and stresses the importance of comparing clinic results with and without scatter correction. Much research has been done on this subject using phantoms, but there are few studies in clinics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 showed that the TEW could make it possible. Our method corresponds to Zaidi et al (8) and stresses the importance of comparing clinic results with and without scatter correction. Much research has been done on this subject using phantoms, but there are few studies in clinics.…”
Section: Discussionmentioning
confidence: 99%
“…So after correction, heart defects could be found. Since King MA et al (3) and Zaidi et al (8) brought a ratio of 0.34 for scattered to unscattered (primary) counts, increase of contrast and sharpness after correction could be understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iterative image reconstruction methods for emission tomography were comprehensively reviewed in [18]. Well-aligned anatomical information from hybrid scanners enabled advances of various correction methods such as attenuation corrections [19] and scatter corrections [20,21] for better quantitative and qualitative imaging [12].…”
Section: Introductionmentioning
confidence: 99%
“…There are several parameters that affect the quality and quantitative accuracy of PET images, including positron range [1], the limited spatial resolution and resulting partial volume effect [2], contribution from scattered photons [3], photon attenuation [4], patient motion [5], and the image reconstruction algorithm [6]. Attenuation of photons in vivo degrades the visual quality and quantitative accuracy of PET images, thereby adversely affecting interpretation and quantitation of activity concentration.…”
Section: Introductionmentioning
confidence: 99%